Sex differences in stretch-induced hypertrophy, maximal strength and flexibility gains - Warneke, Konstantin; Zech, Astrid; Wagner, Carl-Maximilian; Konrad, Andreas; Nakamura, Masatoshi; Keiner, Michael; Schoenfeld, Brad J.; Behm, David George (Frontiers in Physiology, 2023)
If the aim is to increase maximal strength (MSt) and muscle mass, resistance training (RT) is primarily used to achieve these outcomes. However, research indicates that long-duration stretching sessions of up to 2 hours per day can also provide sufficient stimuli to induce muscle growth. In RT literature, sex-related differences in baseline values and adaptations are widely discussed, however, no studies addressing sex-related differences on MSt and MTh could be detected. Therefore, this study aimed to investigate the effects of six weeks of daily (1 hour) unilateral static stretch training of the plantar flexors using a calf-muscle stretching device. Fifty-five healthy (m=28, f=27), active participants volunteered to participate in the study. Maximal strength and range of motion (ROM) were measured with extended and flexed knee joint, and muscle thickness was investigated in the medial and lateral heads of the gastrocnemius. Statistically significant increases in MSt, (p<0.001-0.049, d = 0.45-1.09), ROM (p<0.001-0.037, d = 0.47-1.38) and muscle thickness (MTh) (p<0.001-0.005, d=0.46-0.72) from pre- to post-test were observed with a significant higher increase in MSt, MTh and ROM in male participants, while in pre-test, women showed higher flexibility- and males higher MSt-values. Participants showed more pronounced adaptations in maximal strength and ROM with an extended knee joint as well as MTh in the medial head of the gastrocnemius (p<0.001-0.047). Using relative MSt values (normalized for bodyweight) showed similar results (p <0.001-0.036, d = 0.48-1.03) The positive adaptations can possibly be attributed to stretch-induced mechanical tension induced via passive stiffness of the muscle. Male participants showed lower baseline ROM values, which may be attributed to higher passive stiffness of the muscle, it is speculated that tension may be induced more easily compared to female participants.